Rising above bullying: from despair to recovery - Hayes, Rosemary (Kingsley, 2011)
Extreme bullying can have devastating effects. It can leave a child severely traumatized, their self-esteem destroyed, and in deep despair. This book reveals these shattering effects by telling the stories of eight children who have experienced extreme bullying and then found their way to recovery at a Red Balloon Learner Centre- a place where children can go to continue their education and recover their self-esteem, confidence and feelings of self-worth. Guidance is given on what teachers and parents can do to help a child who is being bullied, or a child who uses bullying behavior, and what the bullied children themselves can do.--[book cover]